2004
DOI: 10.1002/cncr.11943
|View full text |Cite
|
Sign up to set email alerts
|

Association of ampullary and colorectal malignancies

Abstract: Metal ion‐imprinted polymethacrylate beads with sizes ranging from 100 to 300 μm were prepared by suspension polymerization for the application of selective separation of target metal ions. The metal ion contacting area of the beads was enlarged via pore formation (BET 425 m2/g) using toluene as a porogenic agent. The synthesis of the copper‐imprinted porous beads was verified using FTIR, SEM, and ESCA. Separation capacity and selectivity were investigated carrying out column separation experiments. The select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…Das et al [26] reported that persons diagnosed with ampullary cancers are at increased risk of colorectal malignancy and persons with colorectal malignancy are at increased risk of a second primary ampullary cancer, suggesting shared environmental or genetic risk factors. However, colorectal cancers are more common in white and blacks than among Asian-Pacific Islanders and Hispanics [27]; whereas, we found that ampullary cancers were more common among Asian-Pacific Islanders and Hispanics than among other racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 98%
“…Das et al [26] reported that persons diagnosed with ampullary cancers are at increased risk of colorectal malignancy and persons with colorectal malignancy are at increased risk of a second primary ampullary cancer, suggesting shared environmental or genetic risk factors. However, colorectal cancers are more common in white and blacks than among Asian-Pacific Islanders and Hispanics [27]; whereas, we found that ampullary cancers were more common among Asian-Pacific Islanders and Hispanics than among other racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is evidence that sporadic ampullary carcinomas may also associate either synchronously or metachronously with other malignancies such as sporadic colorectal carcinomas [5, 6]. In a population-based study, patients with ampullary cancer were found to be at increased risk for a second primary colorectal cancer and patients with colorectal cancer were found to be at increased risk for a second primary ampullary carcinoma [7]. This bidirectional, greater than chance, mutual association between these two cancers suggests common genetic, environmental or predisposing risk factors or shared mechanisms of carcinogenesis [7].…”
Section: Introductionmentioning
confidence: 99%
“…In a population-based study, patients with ampullary cancer were found to be at increased risk for a second primary colorectal cancer and patients with colorectal cancer were found to be at increased risk for a second primary ampullary carcinoma [7]. This bidirectional, greater than chance, mutual association between these two cancers suggests common genetic, environmental or predisposing risk factors or shared mechanisms of carcinogenesis [7]. Here we describe a rare case of synchronous association of sporadic carcinoma of the papilla of Vater with sporadic colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…FAP and neurofibromatosis are conditions associated with increased risk [1]. Even after excluding FAP patients, the incidence of colonic cancer is doubled in patients with a history of ampullary cancer [38]. Conversely, patients with a history of colon cancer have double the incidence of ampullary cancer [38].…”
Section: Ampullary Carcinomamentioning
confidence: 99%